An alternative description of mass transfer through thick oxide films. (15th April 2015) - Ogawa, Takafumi; Kitaoka, Satoshi; Kuwabara, Akihide; Fisher, Craig A.J.; Moriwake, Hiroki
Abstract : An alternative approach for deriving macroscopic mass transfer expressions in the tradition of Wagner's theory is presented. Starting from a microscopic definition of defect formation energies and carrier species concentrations, the oxygen permeability of α -Al2 O3 thick films under different partial pressures is analyzed. Our formulation reproduces results from permeation experiments that mimic the growth of oxide films on metal alloys, and is more intuitive than previous methods because all micro- and macroscopic factors are directly related to each other.